EFFECTIVENESS OF PERCOLATION PONDS FOR ARTIFICIAL RECHARGE- A CASE STUDY - Tyagi, J.V. (Journal of Soil and Water Conservation, 2022)
Construction of percolation ponds has been carried out extensively in many states of India to augment the ground water recharge in the areas which have limited surface water potential and depend heavily on ground water resources to meet various requirements. In Tamilnadu alone, nearly 10,000 percolation ponds have been constructed so far under various programmes. Two such percolation ponds namely, Uralipatti and Viralipatti in Tamilnadu state were studied to assess the recharge aspects of these ponds in quantitative terms. The data on pond levels, contents, water spread area, rainfall, evaporation and ground water levels of the observation wells were made use of to assess the seepage rates and the extent of influence of these ponds. The seepage rates in Uralipatti and Viralipatti ponds are found to vary from 180 to 16.3 Cu m/day (55.7 to 5.4 inmiday) and 137 to 20.4 Cu m/day (23.3 to 5 mm/day) respectively for storages in these ponds varying between 2700 to 260 Cu in and 10905 to 2830 Cu m respectively. A significant recharge influence is observed in the downstream side of these ponds upto the distances of 340 m in Uralipatti and 200 m in Viralipatti pond respectively